PENGARUH LINGKUNGAN KERJA FISIK DAN NON FISIK TERHADAP KINERJA PEGAWAI KEMENTERIAN AGAMA KOTA PALU - Megawati, Megawati (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
This study aims to determine the effect of Physical Work Environment and Non Physical Work Environment on Employee Performance at the Office of the Ministry of Religious Affairs of Palu City. The method used is an associative method. The type of data used in this study is the qualitative and quantitative data while the data sources used are primary and secondary data. Data analysis technique used is Multiple Linear Regression Analysis. The result of hypothesis analysis and testing can be concluded that: (1) based on the regression test results obtained Sig.F of 0,000 <0.05, which can be interpreted that the variables of Physical Work Environment and non physical work environment simultaneously affect the performance variables. (2) based on the regression test results obtained the physical work environment variable has significance level t sig. (0,000) <? (0.05) and non-physical work environment has a significance level of t sig. (0.000) <? (0,05), so the variable of physical work environment and non working physical environment partially influence to employee performance.